Hardware implementation of multiple fan beam projection technique in optical fibre process tomography - Ruzairi, Abdul Rahim; Mohd Hafiz Fazalul, Rahiman; Lai, Chen Leong; Kok, San Chan; Jon, Fea Pang (Molecular Diversity Preservation International (MDPI), 2009)
Link to publisher's homepage at http://www.mdpi.com